Determination of Some Minerals in Salvadora Persica Stems - Hanaa. S. Boshra,; Yosra Tilal Osman,; AlRasheed El Mohammed, (IJPAR JOURNAL, 2016)
Salvadora persica is a well known small tree in the Middle East, Africa and India subcontinent, it one of most important chewing stick use for oral hygiene by people live in this regions. In this study chemicals analysis for some minerals showed Salvadora Persica collected from three different regions in Sudan (in center, north and west) named as sample No 1,2,3 respectively. The concentrations of four elements Sodium Na +, Potassium K+, Calcium Ca+2, and Magnesium Mg+2 were determined by atomic absorption spectrophotometer using wet digestion method, the results obtained represented presence of four elements with different values. But Sample No 1 showed highest value for Potassium 61.64± 0.025K /ppm, 144.375±0.004 for k/ppm for Sodium and 170.24±0.016 for Calcium, while highest value record ed for Sample No 3 for Magnesium 10.45 K /ppm. The concentrations of fluoride and phosphorus also were determined in the three samples by fluoride selective electrode and UV-visible spectrophotometer. The content of fluoride in samples No 2 and 3 were 3556.56 for both which is higher than sample NO 1, the phosphorus content was found 95 ppm in samples No 1 and 2 higher than sample No 3.